2295. Streptococcus pneumoniae-Related Hemolytic Uremic Syndrome (pHUS) and the Identification of Matched Cross Country Serotypes by Plasma Next-Generation Sequencing (NGS). (26th November 2018) - Yonts, Alexandra; Farnaes, Lauge; Venkatasubrahmanyam, Shivkumar; Hong, David; Hanisch, Benjamin
Abstract: Background: Hemolytic uremic syndrome (HUS) describes a clinical presentation of acute kidney injury, microangiopathic hemolytic anemia and thrombocytopenia. Five to 15% of HUS cases are related to Streptococcus pneumoniae infection, most often meningitis or pneumonia. Despite the introduction of PCV13 and a decrease in invasive pneumococcal disease in children, the incidence of pneumococcal-related HUS (pHUS) cases is rising for unclear reasons. Efforts to determine whether certain serotypes increase the risk of pHUS are often hampered by negative cultures in patients with suspected pneumococcal disease. Direct microbiologic detection methods, such as next-generation sequencing (NGS), may be useful in identifying pHUS cases. We describe four children with pHUS from two institutions that were identified via NGS of cell-free plasma. Methods: Four patients with HUS and negative initial cultures were identified. Blood was sent to Karius (Redwood City, CA) for pathogen detection via plasma NGS. Cell-free DNA was extracted and NGS performed. Human sequences were removed and remaining sequences were aligned to a curated pathogen database including over 1000 organisms. Organisms present above a predefined statistical threshold were reported. For serotyping by NGS, sequences were aligned to a collection of 90 serotype-associated cps alleles. Results: All four patients were found be positive for S. pneumoniae at extremely high levels (Table 1). Three out of four samples were identified as serotype 3 by NGS and similar to the same strain ( SPN034183 ). The fourth sample was consistent with serotype 12A and no strain call was made. Conclusion: In this case series, we report on four patients with pHUS identified via plasma NGS. These cases demonstrate the potential of NGS for pathogen detection and quantitation in plasma to assist in identification of culture-negative infections, as well as the potential to identify clusters of disease that would likely otherwise have gone undetected. *Median MPM in non-HUS S. pneumoniae positive samples over the last 90 days was 1202 MPM Disclosures: S. Venkatasubrahmanyam, Karius, Inc.: Employee, Salary. D. Hong, Karius, Inc.: Employee, Salary.